2019
DOI: 10.1128/aem.03064-18
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity of Vibrio spp. in Sediments of Chinese Marginal Seas

Abstract: Vibrio spp. are ubiquitous marine bacteria with high metabolism flexibility and genome plasticity. Previous studies have revealed the dynamics of planktonic vibrios in relation to environmental forces, such as temperature and salinity. However, little is known about Vibrio ecology in benthic environments. Here, we elucidate the abundance, diversity, and spatial distribution of Vibrio spp. in sediments of the Chinese marginal seas, with a wide spatial range from north to south covering the Yellow Sea (YS), East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 82 publications
3
21
0
Order By: Relevance
“…We observed that the changes in the Vibrio community composition and diversity in relation to seasons were more likely to be a result of a direct influence of temperature, salinity, TDN, DIN, and TDP. Our findings confirmed that salinity was the most important environmental determinant of α-diversity in the Vibrio community as described in previous studies ( Siboni et al, 2016 ; Wang et al, 2019 ), and observed a similar positive correlation (Spearman, p < 0.001). The Bray-Curtis dissimilarity of the Vibrio community was also significantly correlated with temperature in the Maowei sea ( Table 2 Mantel test, p < 0.001) providing further evidence that warmer seawater increased the dissimilarity of the Vibrio community ( Liang et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed that the changes in the Vibrio community composition and diversity in relation to seasons were more likely to be a result of a direct influence of temperature, salinity, TDN, DIN, and TDP. Our findings confirmed that salinity was the most important environmental determinant of α-diversity in the Vibrio community as described in previous studies ( Siboni et al, 2016 ; Wang et al, 2019 ), and observed a similar positive correlation (Spearman, p < 0.001). The Bray-Curtis dissimilarity of the Vibrio community was also significantly correlated with temperature in the Maowei sea ( Table 2 Mantel test, p < 0.001) providing further evidence that warmer seawater increased the dissimilarity of the Vibrio community ( Liang et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Since they drive major biogeochemical cycles and support food webs globally, Vibrio communities are a vital component of the marine ecosystem. Furthermore, the diversity and dynamics of the Vibrio community have attracted growing interest worldwide, including in the Northern Chinese marginal seas, coastal North Atlantic, and Gulf Coast of Mexico ( López-Hernández et al, 2015 ; Vezzulli et al, 2016 ; Wang et al, 2019 ). Understanding when and where pathogenic Vibrio will break out is important for aquaculture and marine health.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio is a ubiquitous group of metabolically flexible marine heterotrophic bacteria, that play an important role in biogeochemical cycling in the ocean. There have been many studies on the diversity and dynamics of Vibrio populations in a variety of marine environments, including the Mid-Atlantic, Mediterranean coast, Australian coast, Japan surrounding seawater, and Chinese marginal seas (Amin et al 2016;Girard et al 2017;Liang et al 2019;Mansergh and Zehr 2014;Siboni et al 2016;Wang et al 2019;Westrich et al 2018). The distribution of Vibrio population in marine environment is influenced by many environmental factors including salinity, temperature, and in some cases the abundance of host organisms (Thompson et al 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…The raw reads were deposited in the National Center for Biotechnology Information Short Read Archive database (accession number PRJNA530319). The raw data were filtered according to the pipeline of Quantitative Insights into Microbial Ecology (Caporaso et al 2010), and read processing was conducted using the method used by Wang et al (2019) and Liu et al (2019).…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%